Dimensi Metrik Graf Dual Prisma - Fenny Fitriani (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2018)
The form of a graph which formed from a graph has no intersecting side is called a dual graph. One graph that can be formed as a dual graph is a prism graph. Prism graph (Pm,n) is a graph formed from the results of a cartesian product of a cycle graph with a line graph. In this paper we discuss the metric dimension of a dual prism graph (P'm,n). The metric dimension of a dual prism graph is divided into two states, when n = 2 and n ≥ 3.